Persepsi Audiens Tentang Proses Migrasi Sistem Penyiaran Nasional Di Indonesia (Studi Fenomenologi Perubahan Migrasi Penyiaran Analog Ke Digital) - Asri, Rahman (Universitas Al Azhar Indonesia, 2023)
The development of digital technology especially in the field of communication, which is growing rapidly has changed the media environment. The newly implemented national digital broadcasting system in Indonesia will also change viewing patterns and audience habits. Aim this study to explain how to audience perceived after switch from analog to digital in broadcasting media. Starting Analog Switch Off (AS0) national broadcasting system with migration process from analog to digital going on November 2nd, 2022. A Long journey to forward to digitalization until governemt policy decided UU Cipta Kerja Omnibus Law on November 22nd, 2020 as legal based for apllied digitalization on broadcasting in Indonesia. This research used Qualitative method with Fenomenology, and the results is positively respond from audiences because with digitalization on broadcasting has more clearly and sharper picture (visual) and audio better than analog.